Morocco : Technical Assistance Report-Monetary and Financial Statistics Mission (July 17-28, 2017). (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultationa highlights deep-rooted weaknesses in the banking system that have undermined economic activity and are now threatening financial stability and fiscal sustainability. Significant deposit outflows have left the banking system with low liquidity, while persistent losses and high levels of nonperforming loans resulted in sizable recapitalization needs, particularly in the state-owned bank. Growth is projected to remain subdued in the coming years, reflecting continued banking sector deleveraging and a less favorable external environment, most notably in Italy. Slow progress in repairing the banking sector and full and up-front recognition of the state's financial commitments to the banking system are the key risks. Urgent actions are needed to restore banking sector viability and credit supply, safeguard public finances, and promote sustained economic growth. It is recommended that the labor supply be strengthened by better targeting social benefits and further relaxing the hiring process for nonresidents.